Desvendando o modo de ação (MOA) cancerígeno do diuron [3-(3,4-Diclofenil)-1,1-Dimetiluréia] no urotélio de ratos - Rocha, Mitscheli Sanches da [UNESP] (2013)
Diuron, a substituted urea herbicide, was carcinogenic to the urinary bladder of Wistar rats at high dietary levels (2500 ppm), with a higher incidence in males. Its proposed carcinogenic mode of action (MOA) includes urothelial cytotoxicity and necrosis followed by sustained regenerative cell proliferation and urothelial hyperplasia. Urothelial cytotoxicity could be induced either by urinary solids or by chemical toxicity by diuron and/or metabolites excreted in the urine. To further elucidate the diuron urothelial MOA in male Wistar rats, this study aimed to: 1) evaluate the possible influence of urinary solids on the development of urothelial lesions; 2) determine the time course and sequence of bladder cytotoxic and proliferative changes; and 3) evaluate the toxicity of the main diuron metabolites on the urothelium. Rats treated with diuron and with NH4Cl for urinary acidification showed decreased urinary pH and reduced amounts of urinary crystals and precipitates. No difference in the incidence of urothelial lesions was found between diuron and diuron+NH4Cl treated groups indicating that cytotoxicity is not due to urinary solids. Rats treated with diuron during 1, 3 and 7 days showed urothelial cell swelling beginning on day 1. Swollen cells at day 7 presented degenerative changes such as distention of the cytoplasm, organelles and nuclei characteristic of cytolysis. By day 28, bladder urothelium in the diuron-treated group showed extensive necrosis, exfoliation and piling up of cells suggestive of hyperplasia. At 8 weeks, the bladder urothelium showed necrosis, exfoliation and significantly increased incidence of simple hyperplasia. The metabolite DCPU was found in rat urine at concentrations above the in vitro IC50 evaluated in a rat urothelial (MYP3) cell line. Moreover, DCPU induced more alterations of gene expression than the other metabolites in rat urothelial cells. Taken together, these results suggest the urothelial carcinogenic MOA of diuron is metabolism to cytotoxic metabolites, producing urothelial cell degeneration, necrosis and exfoliation, followed by sustained regenerative cell proliferation, leading to hyperplasia and eventually tumors after continued diuron exposure.